Imaging peculiarities of gubernaculum tracts in molars as accessional teeth on CT - Masafumi Oda; Ikuko Nishida; Manabu Habu; Osamu Takahashi; Shirou Tabe; Hiroki Tsurushima; Taishi Otani; Daigo Yoshiga; Teppei Sago; Tatsurou Tanaka; Nao Wakasugi‐Sato; Shinobu Matsumoto‐Takeda; et al. (Wiley, 2021)
Abstract Objectives The shapes of gubernaculum tracts (GTs) in molars as accessional teeth remain unidentified. To elucidate imaging peculiarities of GTs in molars with aging on multidetector‐row computed tomography (MDCT). Material and methods This retrospective study was conducted using CT images, including maxillary and mandibular molars, with no abnormal findings from 239 patients. Shapes of alveolar bone, GTs, and dental sacs of the maxillary and mandibular molars were analyzed multi‐sectionally. Correlations between 2‐ and 3‐dimensional imaging figures of GTs in molars and chronological age or stage of molar formation were analyzed. Results Some forms of GTs in maxillary and mandibular third molars were observed. In the early stage, GTs were visualized as bone defect lines on the dentition and grooves on the mesial alveolar crest continuous with the dental sac to mesial tooth bud. GTs of the third molar formed a J‐shape in maxillary teeth and Y‐shape in mandibular teeth in the middle stage, as alveolar bone around the GT developed. In the mature stage, the course of the GT changed to straight and perpendicular. Some GT forms were also identified in first and second molars. Significant correlations were found between GT alterations and chronological age or stage of molar formation. Moreover, tracts continuing from the distal side of mandibular third molars were detected. Conclusions This paper describes the peculiarities and process of progression for GTs in molars, and the existence of tracts continuing from the distal side of mandibular third molars, unlikely dentition with deciduous predecessors. These preliminary data should prove beneficial for studies focusing on GTs in molars.